Stress and Sleep in Addictive Behavior and Application of Yoga-based Interventions: A Short Narrative Review - Gaihre, Ananda; Sasidharan, Rajesh Kumar; Bista, Suman; Khadka, Rakshya; Poudel, Lisasha; Bista, Sujana; Sapkota, Vijaya (One Health Journal of Nepal, 2021)
Individuals who attempt to change their addictive behaviour frequently undergo relapse. There is substantial evidence that stress and sleep plays a crucial role in the relapse. The stressful situation and poor sleep quality represent a risk factor factor that may play a critical role in predicting individuals success in abstaining.Diagnosing and treating stress and sleep disorders will have a significant impact on the management of addictive behaviour. The extent of impairments at biopsychosocial- spiritual levels. Therefore it needs to be recognized and addressed in an individual at the physical, psychological, social and spiritual levels. Recent studies have shown yoga as a promising complimentary therapy for treating and preventive addictive behaviors at biopsychosocial-spiritual levels. Yoga may work on addictive behaviour through down-regulation of the hypothalamic-pituitary-adrenal (HPA) axis and bringing a state of parasympathetic nervous system (PNS) dominance.